New Nano-Precipitates Hardened Steels of Wide Rangeof Strength and Toughness and High Resistance to Piercing With Projectiles - Jarosław MARCISZ (Wojskowa Akademia Techniczna, 2012)
Results of tests of mechanical properties and resistance to perforation with small-calibre armour-piercing projectiles for new designed grades of nano-precipitates hardened steels have been presented. The results comprise of mechanical properties essential for materials used in armour and microstructure which influences the mechanisms of piercing. Plate segments of high-alloyed maraging steels and low-carbon Ni-Mo steels were produced using semi-industrial lines for melting, casting and thermo-mechanical treatment. Plate segments were produced with the use of different parameters of final heat treatment in order to achieve a wide range of mechanical properties. Preliminary assessment of the protection capability concerning piercing was carried out based on the results of firing tests with 12.7 mm B-32 incendiary projectiles at square steel plates of 50÷150 mm in dimension and of 5÷10 mm in thickness placed on an RHA (Armox 500T and Armox 600T) “witness” plate. A minimal thickness of plates which protected the “witness” plate and did not fragment was determined. The microstructure in the area of the projectile impact was examined. The usability of newly designed grades of steel in layered armour and the possibilities of the production of these plates from the steel in domestic steel plants were pointed out.
Keywords: Badania stali pancernej